2022
DOI: 10.1029/2022gl099282
|View full text |Cite
|
Sign up to set email alerts
|

A Raman Spectroscopic and Microimage Analysis Perspective of the Chang'e‐5 Lunar Samples

Abstract: The Chang'e‐5 (CE‐5) materials represent the youngest returned lunar samples. We performed a detailed Raman spectroscopic survey (1259‐point Raman modal analysis) to evaluate the mineralogical characteristics of CE‐5 soils, constraining the source materials and shock effects of these unique samples. The mineral chemistry (e.g., Mg#3‐60 for mafic minerals) and modal abundance (first distinguishing basaltic and feldspathic glasses) of CE‐5 mare soils are different from those of Apollo high‐ and low‐Ti basalts, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
(115 reference statements)
0
7
0
2
Order By: Relevance
“…Our observations showed that there were very few spherical iron-sulfide grains in the Chang’E-5 lunar fines, and only two magnetite-bearing spherical iron-sulfide grains were found in the studied samples. We suggest that the two main reasons for the weaker magnetic field strength in the Chang’E-5 region are as follows: (1) Lunar magnetic field anomalies are spatially correlated with large-impact ejecta, but only a few distant ejecta from large-impact craters are mixed in the Chang’E-5 sampling region 23 . (2) Chang’E-5 lunar soil has a young age of formation, and the possibility of the presence of an effective external magnetic field (generated by ancient core dynamics or basin-forming impacts) is relatively low.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our observations showed that there were very few spherical iron-sulfide grains in the Chang’E-5 lunar fines, and only two magnetite-bearing spherical iron-sulfide grains were found in the studied samples. We suggest that the two main reasons for the weaker magnetic field strength in the Chang’E-5 region are as follows: (1) Lunar magnetic field anomalies are spatially correlated with large-impact ejecta, but only a few distant ejecta from large-impact craters are mixed in the Chang’E-5 sampling region 23 . (2) Chang’E-5 lunar soil has a young age of formation, and the possibility of the presence of an effective external magnetic field (generated by ancient core dynamics or basin-forming impacts) is relatively low.…”
Section: Discussionmentioning
confidence: 93%
“…X-ray diffraction and Raman spectroscopy results have shown that iron-sulfide is a minor component of Chang’E-5 soil samples 21 23 . Several angular and spherical iron-sulfide grains were selected by scanning electron microscopy (SEM) in our study (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4,15 However, the Chang'E-5 basalts have higher TiO 2 , but lower MgO contents, than Apollo low-Ti basalts (Figure 6), possibly owing to one or more factors, including different crystallization processes, diverse abundance of ilmenite-bearing cumulate in their mantle sources, different melting depths, or partial melting degrees. 15,42 These results obtained by applying the new method to a large quantity of lunar clasts furnish additional accurate information for the petrogenesis of the Chang'E-5 basalts and the lunar thermal state during Moon's middle age.…”
Section: ■ Validation Of the Algorithmmentioning
confidence: 99%
“…Our new robust results document that the Chang’E-5 basalts are the low-Ti type. This interpretation is consistent with the presence of Cr-spinel in the basalt clasts, low TiO 2 contents (∼4.4 wt %) in their parental magmas, and the bulk chemical analysis of lunar soils. , However, the Chang’E-5 basalts have higher TiO 2 , but lower MgO contents, than Apollo low-Ti basalts (Figure ), possibly owing to one or more factors, including different crystallization processes, diverse abundance of ilmenite-bearing cumulate in their mantle sources, different melting depths, or partial melting degrees. , These results obtained by applying the new method to a large quantity of lunar clasts furnish additional accurate information for the petrogenesis of the Chang’E-5 basalts and the lunar thermal state during Moon’s middle age.…”
Section: Application To Chang’e-5 Basalt Clastsmentioning
confidence: 99%
“…Until 2022, no Raman payload has been applied to lunar robotic exploration missions; however, Raman spectroscopy has been widely used in scientific research on meteorites (Ling & Wang, 2015; Rull et al., 2004), returned samples (H. Cao et al., 2022; Ling et al., 2011), and laboratory analogs (Shi et al., 2020) in laboratory. Surveys such as those conducted by Fabel et al.…”
Section: Introductionmentioning
confidence: 99%